Solubility of Methane in Alkylpyridinium-Based Ionic Liquids at Temperatures between 298.15 and 343.15 K and Pressures up to 4 MPa - Kurnia, K.A. (American Chemical Society, 2020)
Ionic liquids (ILs) are promising solvents for gas absorption and separation processes. In this work, the solubility of methane in four alkylpyridinium-based ILs, namely, 1-butylpyridinium bis(trifluoromethylsulfonyl)imide (C4pyTf2N), 1-hexylpyridinium bis(trifluoromethylsulfonyl)imide (C6pyTf2N), 1-butylpyridinium tetrafluoroborate (C4pyBF4), and 1-hexylpyridinium tetrafluoroborate (C6pyBF4), was measured at temperatures 298.15 to 343.15 K and pressures up to 4 MPa using a pressure drop method. The result showed that the solubility of methane increases with increasing pressure and decreasing temperature. In addition, the solubility of methane in ILs can be ranked as follows: C4pyBF4 < C6pyBF4 < C4pyTf2N < C6pyTf2N. Furthermore, Henry's law constant (KH) and thermodynamic properties, namely, enthalpy and entropy at an infinite dilution, were estimated from the experimental solubility data. The estimated thermodynamic properties revealed that the solubility of methane in alkylpyridinium-based ILs is not only governed by a favorable solute-solvent interaction but also balanced by an unfavorable entropy of solution. Copyright Â© 2020 American Chemical Society.